African Handbook of Climate Change Adaptation 2021
DOI: 10.1007/978-3-030-45106-6_113
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous and Scientific Forecasts on Climate Change Perceptions of Arable Farmers: Rwenzori Region, Western Uganda

Abstract: Despite the dissemination of climate information from national meteorological systems, arable farmers still have challenges of dealing with climate-related risks. This study investigated the effect of using indigenous knowledge-based forecasts (IFs) and scientific knowledge-based forecasts (SFs) on the climate change perceptions of arable farmers in the Rwenzori region, Western Uganda. Data on socio-economic characteristics, use of forecasts, and climate change perceptions was collected from 580 arable farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Knowledge of shrimp farmers about climate change and its risks is very important and has the potential to be a factor in making decisions, as well as plans for agricultural and fisheries development (Mahmood et al, 2020;Mekonnen et al, 2021;Ogunpaimo et al, 2021;Atube et al, 2021;Zhu et al, 2021). Considering the perceptions of farmer households in designing adaptation policies, will produce a useful adaptation response and potentially minimize the risk of climate change in a sustainable manner (Ali et al, 2021;Addis and Abirdew, 2021;Nkuba et al, 2021). This study has designed the questions presented in the questionnaire and asked during the interview process (see points in Table 4).…”
Section: Farmer Perceptions Of Climate Changementioning
confidence: 99%
“…Knowledge of shrimp farmers about climate change and its risks is very important and has the potential to be a factor in making decisions, as well as plans for agricultural and fisheries development (Mahmood et al, 2020;Mekonnen et al, 2021;Ogunpaimo et al, 2021;Atube et al, 2021;Zhu et al, 2021). Considering the perceptions of farmer households in designing adaptation policies, will produce a useful adaptation response and potentially minimize the risk of climate change in a sustainable manner (Ali et al, 2021;Addis and Abirdew, 2021;Nkuba et al, 2021). This study has designed the questions presented in the questionnaire and asked during the interview process (see points in Table 4).…”
Section: Farmer Perceptions Of Climate Changementioning
confidence: 99%
“…Determining local knowledge, perceptions and awareness of climate change in the local community is key to understanding local concerns about the phenomenon and developing locally relevant climate change adaptation solutions. Indeed, evidence has shown that the influence of indigenous and local knowledge in sector-specific climate change adaptation is high in some African counties including Kenya and shows high evidence of risk reduction (Nkuba et al , 2021; Zvobgo et al , 2022). Local communities’ knowledge can also help to provide information about context-specific climate change impacts.…”
Section: Introductionmentioning
confidence: 99%